Growth potential of mixed microalgae cultivated in domestic wastewater with nutrient supplementation under Malaysian weather conditions - Shabnam, Sohana (2017)
Microalgae are considered to be potential biocatalyst for the production of renewable biofuel along with other valuable products. For sustainable algal production, optimization of the algal growth with cost effective harvesting is crucial. An attempt was made to evaluate the effect of nutrients on biomass production of photoautotrophic mixed microalgae using domestic wastewater as feed-stock under varying weather conditions in open pond system. The objectives were to - i) study the effects of concentration and ratio of nitrogen and phosphorus on growth and biomass production, ii) find out the most efficient flocculating agent for effective harvesting, iii) examine the proximate composition of harvested biomass and iv) evaluate the microalgae composition and diversity prevailed under nutrient adjustments while culturing microalgae in wastewater under weather variations. In order to achieve the objectives, microalgae were collected from wastewater pond and cultured in three different weather conditions (dry, wet and mixed). Nitrogen and phosphorus treatments in wastewater were taken in two different ratios (0.77:1 and 5:1) with increasing concentrations (N and P concentration ranges from 10.30 to 41.20 ppm and 2.06 to 53.12 ppm respectively). Bold Basal Medium (BBM) and original wastewater were taken as control. Meanwhile, four flocculating agents namely FeCl3, alum, Ca(OH)2 and Aflok® (organic flocculant) were investigated to find out the most efficient one for harvesting microalgae considering different pH condition, dosage, algal concentration and sedimentation time. The mixed microalgae diversity under given treatments and weather variations was also closely observed during the culture periods. It was found that, the increase of nutrients concentration in the medium increased the final algal biomass regardless the weather condition. Whereas, significantly higher biomass (>0.60 g/L) obtained where the N : P ratio was greater (5:1). The results from harvesting efficiency of flocculants indicated that, FeCl3 and Aflok® at their minimal dosage (<0.08 g/L and <0.112 g/L respectively) were more effective compared to alum and Ca(OH)2 under wide environmental variations of the medium. In proximate analysis, it was found that protein content increased with increasing nutrient concentration but lipid and carbohydrate increased when nutrients are in depleted condition. The highest protein, lipid and carbohydrate content were found to be 26.89%, 32.07% and 37.47% respectively. In species composition, the Chlorophyta division was observed to be the largest (62.5% - 90%) microalgae group encountered both in terms of abundance and frequency occurrence regardless of weather variations. The genus Chlorella vulgaris was the most dominant species that sustained in all treatments culture due to their resiliency to the media conditions. The species richness was observed to be higher in treatments with higher nutrient content than in treatments with lower value. Meanwhile, diversity indices were found to be lower in both low and high nutrient treatments. However, higher diversity indices were found in treatments with comparably moderate nutrients content, which indicated uneven distribution of microalgae species in lower and higher nutrient treatments. It can be concluded that, when mixed algae is cultivated in open pond system, both the nutrient concentration and ratio are dominating factors that can highly influence the microalgae biomass growth, their biochemical composition as well as their community structure. Therefore, by regulating the nutrients and applying effective harvesting technique sustainable microalgae biomass production is possible from mixed algae culture in wastewater.